2018
DOI: 10.3390/mi9040155
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic Flow of Viscoelastic Fluid in a Nanoslit

Abstract: The electroosmotic flow (EOF) of viscoelastic fluid in a long nanoslit is numerically studied to investigate the rheological property effect of Linear Phan-Thien-Tanner (LPTT) fluid on the fully developed EOF. The non-linear Poisson-Nernst-Planck equations governing the electric potential and the ionic concentration distribution within the channel are adopted to take into account the effect of the electrical double layer (EDL), including the EDL overlap. When the EDL is not overlapped, the velocity profiles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…The high Weissenberg number problem (HWNP) loses numerical accuracy and stability under relatively high Wi [35,52]. The Log Conformation Reformulation (LCR) method [52,53] has proven to be one of the most effective strategies for overcoming this problem, and the procedure is presented as follows.…”
Section: Numerical Methods and Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high Weissenberg number problem (HWNP) loses numerical accuracy and stability under relatively high Wi [35,52]. The Log Conformation Reformulation (LCR) method [52,53] has proven to be one of the most effective strategies for overcoming this problem, and the procedure is presented as follows.…”
Section: Numerical Methods and Code Validationmentioning
confidence: 99%
“…Li et al [34] studied the transient flow of Maxwell fluid in a long, straight microchannel and the effect of relaxation time. Mei et al [35] analyzed the EOF characteristics of Linear Phan-Thien-Tanner (LPTT) fluids in a nanoslit with EDL overlap.…”
Section: Introductionmentioning
confidence: 99%
“…They later [ 8 ] reported an approximate analytical solution to a similar flow in a slit microchannel. Mei et al [ 9 ] studied the electroosmotic flow of a linear Phan–Thien–Tanner fluid in a nanoslit by solving numerically the nonlinear Poisson–Nernst–Planck equations. Matías et al [ 10 ] presented a perturbation analysis of Joule heating effects on electroosmotic flow in a microcapillary tube filled with immiscible Newtonian and power-law fluids.…”
Section: Linear Electrokinetic Phenomena (Seven Papers)mentioning
confidence: 99%
“…The power‐law model was also used in the literatures and , in which the analytical solution for velocity distribution of the electroosmosis flow in a slit microchannel is obtained. Furthermore, in the analytical and numerical study on electroosmotic flow of viscoelastic fluid, Maxwell fluid model , Oldroyd‐B model , and the Phan–Thien–Tanner fluid model were also extensively considered to describe the rheological behavior of fluids. The experimental study on electroosmotic flow of non‐Newtonian fluids can also be found in .…”
Section: Introductionmentioning
confidence: 99%